Bilingualisme dan Multilingualisme dalam Masyarakat Kabupaten Subang - Septia Eka Anggun Yusnia; Sumaryoto Sumaryoto; Sumaryati Sumaryati (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
This study aims to describe the condition of bilingualism and multilingualism, as well as language attitudes in the people of Subang. The research was conducted using a qualitative descriptive method. The data source is a list of the intensity of language use and language attitudes used by the people in Subang in their daily interactions. Respondents in this study amounted to 103 respondents based on social indices such as differences in gender, age, and level of education. The research instrument used is the instrument "Basa Urang" from Chon. The data analysis of this study used the model recommended by Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. The results of the study concluded as follows: 1) the people of Subang are bilingual and multilingual people; 2) the language attitude of the people of Subang to local languages, national languages, and foreign languages tends to be positive. Keywords: bilingualism, multilingualism, language attitudes, siciolinguistics